Creating an Academic Department Vision: Processes, Challenges, Rewards - Costas Spirou; Steve McLaughlin (Academic Chairpersons Conference Proceedings, 2023)
Department chairs are expected to lead academic units by managing numerous aspects of the academic enterprise. Participants in this session will focus on the process of creating a department vision that is inclusive by engaging various stakeholders while considering the university/college strategic plan and other institutional initiatives.
Keywords: Leadership; Planning; Institutional Development; Faculty/Student Success; Impact/Effectiveness